Implant Surface Temperature Changes during Er:YAG Laser Irradiation with Different Cooling Systems - Monzavi, Abbas (Tehran University of Medical Sciences, 2014)
OBJECTIVE: Peri-implantitis is one of the most common reasons for implant failure. Decontamination of infected implant surfaces can be achieved effectively by laser irradiation; although the associated thermal rise may cause irreversible bone damage and lead to implant loss. Temperature increments of over 10ºC during laser application may suffice for irreversible bone damage. PURPOSE OF STUDY: The purpose of this study was to evaluate the temperature increment of implant surface during Er:YAG laser irradiation with different cooling systems. MATERIALS AND METHODS: Three implants were placed in a resected block of sheep mandible and irradiated with Er:YAG laser with 3 different cooling systems namely water and air spray, air spray alone and no water or air spray. Temperature changes of the implant surface were monitored during laser irradiation with a K-type thermocouple at the apical area of the fixture. RESULTS: In all 3 groups, the maximum temperature rise was lower than 10°C. Temperature changes were significantly different with different cooling systems used (P<0.001). CONCLUSION: Based on the results, no thermal damage was observed during implant surface decontamination by Er:YAG laser with and without refrigeration. Thus, Er:YAG laser irradiation can be a safe method for treatment of periimplantitis.